Antisera against Neisseria gonorrhoeae cross-react with specific brain proteins of the common marmoset monkey and other nonhuman primate species - Reuss, Bernhard; Schwerk, Christian; Schroten, Horst (Brain research, 2016)
Prenatal maternal infections with Neisseria gonorrhoeae (NG) correlate with an increased lifetime probability for the offspring to develop psychosis. We could previously demonstrate that in human choroid plexus papilloma cells, anti-NG antibodies (α-NG) bind to mitochondrial proteins HSP60 and ATPB, and interfere with cellular energy metabolism. To assess the in vivo relevance for this, especially during prenatal neural development, we investigated here interactions of NG-specific antisera (α-NG1, α-NG2) with brain, choroid plexus and other non-neural tissues in pre- and perinatal samples of the nonhuman primate (NHP) Callithrix jacchus (CJ), a NHP model for preclinical research. In histological sections at embryonic day E75, immunohistochemistry revealed α-NG1 and -2-staining in choroid plexus, ganglionic hill, optic cup, heart, and liver. Within the cells, organelle-like structures were labeled, which could be identified by immunohistochemical double-labeling as mitochondria. Both one- and two-dimensional Western blot analysis revealed tissue specific patterns of α-NG1 immunoreactive bands and spots, respectively, which were subsequently characterized by mass spectrometry. Thereby we could confirm the interactions of α-NG1 with human HSP60 and ATPB also in CJ choroid plexus and liver. Even more important, in the CJ brain, several new targets, including NCAM1, CRMP2, and SYT1, were identified, which by unrelated studies have been previously suggested to correlate with an increased schizophrenia risk. These findings support the idea that the marmoset monkey is a useful NHP model to investigate the role of maternal bacterial infections during prenatal brain development, and thereby might improve the understanding of this important aspect of schizophrenia pathology.